Timed barium oesophagram: better predictor of long term success after pneumatic dilation in achalasia than symptom assessment. Issue 6 (1st June 2002) - Vaezi, M F; Baker, M E; Achkar, E; Richter, J E
Abstract : Background: Symptom relief post pneumatic dilation is traditionally used to assess treatment success in achalasia patients. Recently, we showed that symptom relief and objective oesophageal emptying are concordant in about 70% of patients, while up to 30% of achalasia patients report near complete symptom relief despite poor oesophageal emptying of barium. Aims: We now report the results of long term clinical follow up in these two groups of achalasia patients, assessing differences in symptomatic remission rates. Methods: Achalasia patients undergoing pneumatic dilation since 1995 were evaluated both symptomatically and objectively at regular intervals. Pre and post dilation symptoms were recorded. Barium column height was measured five minutes after ingesting a fixed volume of barium per patient to assess oesophageal emptying. Patients who initially reported near complete symptom relief were divided into two groups based on objective findings on barium study: (1) complete oesophageal emptying (concordant group), and (2) poor oesophageal emptying (discordant group). Patients were followed prospectively for symptom recurrence. Results: Thirty four patients with complete symptom relief post pneumatic dilation were identified. In 22/34 (65%) patients, the degree of symptom and barium height improvements was similar (concordant group). In 10/34 (30%) patients, there was < 50% improvement in barium height (discordant group). Significantly (p<0.001) more discordant (9/10; 90%) than concordant (2/22; 9%) patients failed therapy at the one year follow up. Seventeen of 22 (77%) concordant patients were still in remission while all discordant patients had failed therapy by six years of follow up. Length of time in symptom remission (mean (SEM)) post pneumatic dilation was significantly (p=0.001) less for the discordant group (18.0 (3.6) months) compared with the concordant group (59.0 (4.8) months). Conclusions: (1) Poor oesophageal emptying is present in nearly 30% of achalasia patients reporting complete symptom relief post pneumatic dilation. (2) The majority (90%) of these patients will fail within one year of treatment. (3) Timed barium oesophagram is an important tool in the objective evaluation of achalasia patients post pneumatic dilation.